Real-world evidence for beneficial effects of dipyrone in 4,278 patients with pulmonary hypertension – Analysis of the risk of ventilation, hospitalization, and agranulocytosis - Hertel, Moritz; Preissner, Saskia; Gohlke, Björn O.; Kuebler, Wolfgang M.; Hernandez, Gema; Akyüz, Mehmet; Preissner, Robert (European journal of pharmacology, 2023)
Dipyrone has been used as an analgesic for a century, but recently was proposed as a novel therapeutic strategy for the prevention and therapy of pulmonary hypertension (PH). The aim of this study was to analyze whether the risk for ventilation procedures and hospitalization was lower among patients with PH who used dipyrone compared to subjects who did not use dipyrone. Initially, patients with PH were retrieved from the TriNetX database, whereby subjects who used dipyrone were assigned to cohort I, and cohort II was formed by those individuals who did not use dipyrone. Both cohorts were matched for several variables. The outcomes were requirement for ventilation procedures and hospital admission, whereby the time window to record events was 5 years after diagnosis of PH. Subsequently, risk analysis was carried out, and risk ratio (RR) and odds ratio (OR) were calculated. In addition, the risk of agranulocytosis was determined for both cohorts. Out of 741,875 individuals diagnosed with PH 4,282 and 737,593 patients were assigned to the cohorts I and II. After matching, each cohort accounted for 4,278 individuals. Among the cohorts I and II 10 and 187 individuals required ventilation procedures. The according risks of 0.2% vs. 4.4% were significantly different (p < 0.0001; Log-Rank test). RR and OR were 0.053 and 0.051. Within the cohorts I and II 10 and 1,195 subjects required hospital admission. The risks of hospitalization of 0,4% vs. 27.9% differed significantly (p < 0.0001). RR and OR were 0.016 and 0.012. Among the cohorts I and II 47 and 66 individuals were diagnosed with agranulocytosis, whereby no significance was found (p > 0.05). The risk for ventilation measures and hospitalization among patients with PH was found to be significantly lower when dipyrone was used. Even though the underlying mechanisms remain unknown to date, they are supposedly mediated by an active metabolite of dipyrone. The obtained results appear to be promising for patients suffering from PH. Hence, the present study may encourage further research. •We analyzed real-world data of patients with pulmonary hypertension with and w/o dipyrone.•To determine whether the risk for ventilation and hospitalization was lower when dipyrone was used.•We found the risk for ventilation and hospitalization significantly lower when dipyrone was used.•These results may encourage further research.